Ketepatan penggunaan preposisi dalam karangan siswa kelas III, IV, V, dan VI - Sumadi, Sumadi; Susilowati, Novi Eka (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
This study aims at describing the appropriate and correct use of prepositions in elementary school students’ composition. The design of this study is qualitative research combined with formal approaches for students in grade 3, 4, 5 and 6. The results of the study indicate that (1) there is a preposition used in all grades; (2) there are some prepositions used in certain grade; (3) some preposition functions are found in all grades; and (4) some preposition functions are found in certain grades.